2018
DOI: 10.1177/2470289718820845
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Associations Between Stress and Cardiovascular Risk Factors and Outcomes

Abstract: Psychological stress, a subjective perception of an adverse environmental change, is a hallmark of modern society. Although psychological stress has previously been established as a risk factor for cardiovascular disease (CVD), it is unclear whether stress influences cardiovascular risk differently in men versus women. Gender disparities exist in the prevalence of stress as well as in the prevalence and prognosis of CVD; therefore, associations between stress and CVD risk and mortality may vary by sex. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
1
7
2
2
Order By: Relevance
“…In contrast to a prior study that reports the influence of stress on sedentary behaviors is stronger among men, 46 we found that women in our sample are more likely to be in the physically inactive group than men. Women likely tend to be physically inactive when ETV is the stressor, and the safety of the neighborhood is of concern.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to a prior study that reports the influence of stress on sedentary behaviors is stronger among men, 46 we found that women in our sample are more likely to be in the physically inactive group than men. Women likely tend to be physically inactive when ETV is the stressor, and the safety of the neighborhood is of concern.…”
Section: Discussioncontrasting
confidence: 99%
“…In our sample, the association between stressful life events and cardiovascular problems was comparable in female and male participants. This is supported by other studies showing a significant effect of stress on cardiovascular health in both men and women [44].…”
Section: Discussionsupporting
confidence: 87%
“…Our results showed that a 13-weeks, aerobic PhE program is able to counteract the effects of estrogen depletion on the CV system, which are considerably associated with the development of arterial stiffness, diastolic dysfunction and heart failure with preserved ejection fraction [ 38 ]. Moreover, we observed an improvement in metabolic profile, especially in terms of HC, leptin, leptin/FM and cortisol, the latter being a causal risk factor for CVD, especially in women [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%